Preparation method of nickel-carbon conductive shielding foam
By using nickel-carbon nanotube cerium oxide composite materials in ultra-thin conductive foam and introducing self-repair materials, the problems of foam in high-frequency electromagnetic shielding and long-term stability are solved, and efficient electromagnetic shielding and self-repair functions are achieved.
Patent Information
- Application Number
- CN202411814414.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-11
AI Technical Summary
The existing ultra-thin conductive foam is poor in shielding high-frequency electromagnetic interference, and has poor long-term stability under mechanical stress and temperature changes, which can easily lead to damage and degradation of conductive properties.
A nickel-carbon nanotube cerium oxide composite material is used, and polyfuran and maleimide are introduced to construct a self-healing system. The conductive network is automatically repaired through the reverse Diels-Alder reaction to restore the shielding performance and conductivity of the material.
It significantly improves the electromagnetic shielding performance of foam, extends service life, maintains long-term and stable shielding effect, and enhances the material's anti-aging and environmental resistance.
Smart Images

Figure CN119277748B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of conductive foam, and in particular to a method for preparing nickel-carbon conductive shielding foam. Background Art
[0002] With the rapid development of electronic technology, various electronic devices are increasingly used in life and industry. With the increase of functional integration and complexity of equipment, electromagnetic interference (EMI) problems are becoming more and more serious. Electromagnetic interference is mainly caused by electromagnetic radiation or conductive interference signals generated by electronic equipment, which may interfere with the normal operation of other equipment, resulting in functional failure, data loss or signal error. In order to suppress electromagnetic interference and ensure the normal operation of electronic equipment, electromagnetic shielding technology has become a key part of electronic product design.
[0003] As an excellent electromagnetic shielding material, conductive foam is widely used in electromagnetic shielding due to its good conductivity, flexibility and shock absorption. However, as electronic products develop towards lighter and more integrated trends, the shell design of these devices is more compact, and the gaps between internal components are also shrinking. This design trend has put forward new and higher requirements on the size and performance of conductive foam, especially in the application of ultra-thin foam (foam thickness ≤ 0.8mm).
[0004] Ultra-thin conductive foams face several challenges in trying to achieve smaller sizes. First, as the thickness decreases, the conductive material content in the foam decreases accordingly, which often leads to discontinuous conductive paths, which directly affects the electromagnetic shielding effectiveness. The operating frequency of modern electronic devices continues to increase, and the requirements for electromagnetic shielding effectiveness are also increasing accordingly. Existing ultra-thin conductive foams often cannot meet the requirements in shielding high-frequency electromagnetic interference.
[0005] Secondly, in order to achieve ultra-thin characteristics, the thickness of the substrate is usually reduced during the production process of conductive foam. Although this meets the space requirements of thin and light devices to a certain extent, the mechanical strength of the material is greatly reduced, making the ultra-thin conductive foam very easy to break and tear during installation and use, which not only leads to the loss of shielding performance, but also may affect the reliability and stability of the overall equipment.
[0006] In addition, the long-term stability of ultra-thin conductive foam is also an important consideration. Such materials usually need to be used in a constantly changing temperature and mechanical stress environment, which may cause the material to crack, age, or reduce its conductivity. Especially for ultra-thin conductive foam, due to its large surface area to volume ratio, it is more susceptible to external environmental factors, and its long-term stability is poor, which further aggravates the degradation of material performance. Summary of the invention
[0007] The present invention provides a method for preparing a nickel-carbon conductive shielding foam, which adopts a specific material combination and manufacturing process, not only improving the electromagnetic shielding performance of the ultra-thin conductive foam, but also constructing a self-repairing system by introducing self-repairing materials such as polyfuran and maleimide. This system can automatically repair the conductive network through the reverse Diels-Alder reaction when the foam is subjected to mechanical stress or thermal cycling to produce cracks, restore the shielding performance and conductivity of the material, thereby effectively extending the service life of the foam and maintaining its long-term stable shielding effect.
[0008] The purpose of the present invention is mainly achieved through the following technical solutions:
[0009] A method for preparing a nickel-carbon conductive shielding foam comprises the following steps:
[0010] S1: pretreated carbon nanotubes and cerium oxide nanoparticles are mixed in proportion, and nano nickel powder is added to form a suspension; a reducing agent is added under stirring conditions to perform a reduction reaction, so as to deposit nickel ions on the surfaces of the carbon nanotubes and cerium oxide particles to obtain a nickel-carbon nanotube-cerium oxide composite powder;
[0011] S2: After mixing the nickel-carbon nanotube-cerium oxide composite powder with the ionic liquid dispersant, use ultrasonic dispersion; then mix the silicone oil and silicone rubber as a matrix, then gradually add polyfuran and maleimide to the matrix, and add a silane coupling agent to fully combine; add the dispersed composite powder to the silicone matrix, continue stirring until the mixture is uniform, then add a platinum catalyst and a cross-linking agent, and pour the mixture into a mold to solidify to form a foam;
[0012] S3: Paste the conductive layer, coat the foam with epoxy resin adhesive and then heat press the conductive layer onto one side of the foam;
[0013] S4: Setting an adhesive layer, using an acrylic-based pressure-sensitive adhesive, coating it on the other side of the foam and curing it;
[0014] S5: Setting an isolation layer, and using a light pressure laminator to laminate the isolation layer to the adhesive layer.
[0015] In one or more embodiments, the specific process of step S1 is: adding carbon nanotubes into deionized water, adding sodium dodecyl sulfate and then using ultrasonic processing equipment to ultrasonically treat the carbon nanotubes for 1-2 hours. After the ultrasonic treatment is completed, the dispersed carbon nanotubes are washed 2-3 times.
[0016] The cerium oxide nanoparticles were added to deionized water, stirred for 30-60 min using a mechanical stirrer, and then treated with ultrasound for 30-60 min.
[0017] The pretreated carbon nanotubes and cerium oxide nanoparticles are mixed in a mass ratio of 1:0.5-1.5, and nano nickel powder is added to the carbon nanotube-cerium oxide mixed solution to form a suspension. The mass ratio of the pretreated carbon nanotubes and nano nickel powder is 1:10-12.
[0018] Under stirring conditions, a reducing agent is gradually added to carry out a reduction reaction, the reaction temperature is controlled at 80-100°C, and the time is 2-3 hours, so that nickel ions are deposited on the surface of carbon nanotubes and cerium oxide particles to form a uniformly coated nickel-carbon nanotube-cerium oxide composite structure. Preferably, the reducing agent is at least one of hydrogen, ethylene glycol and formic acid.
[0019] In one or more embodiments, the specific process of step S2 is to use ultrasonic dispersion for 30-60 minutes to disperse 25-40 parts of nickel-carbon nanotube-cerium oxide composite powder and 1-5 parts of ionic liquid dispersant by weight; preferably, the ionic liquid dispersant is at least one of 1-butyl-3-methylimidazolium hexafluorophosphate, 1-ethyl-3-methylimidazolium tetrafluoroborate and 1-hexyl-3-methylimidazolium chloride.
[0020] 10-25 parts of organic silicone oil and 20-40 parts of silicone rubber are uniformly mixed to form a matrix material; preferably, the organic silicone oil is one of dimethyl silicone oil, methylphenyl silicone oil and vinyl silicone oil. The silicone rubber is one of methylvinylsiloxane and methylphenylsiloxane.
[0021] 5-10 parts of polyfuran and 5-10 parts of maleimide are gradually added into the mixture of silicone oil and silicone rubber, and stirred evenly at 60-80°C.
[0022] Then add 0.5-3 parts of silane coupling agent, continue stirring, make the silane coupling agent and the matrix fully combined, gradually add the dispersed nickel-carbon nanotube-cerium oxide composite powder to the organic silicon matrix mixture, continue stirring until completely mixed, stirring speed 500-1000r / min; stirring time 30-60min, add 0.01-0.05 parts of platinum catalyst to the mixed matrix and composite powder, and gently stir evenly, then add 0.2-1.5 parts of cross-linking agent, fully mix; pour the mixture into the mold for curing and molding. Preferably, the silane coupling agent is one of KH-550, KH560 and KH570. The cross-linking agent is methyltriethoxysilane. The curing conditions are curing at 60-80°C for 1-3h, humidity ≤50%RH, and avoid bubble formation.
[0023] In one or more embodiments, the specific process of step S3 is to select conductive cloth as the conductive layer, align the conductive cloth with the foam surface, coat the back of the conductive cloth with epoxy resin adhesive, and perform hot pressing at 120℃-140℃ and 5-6MPa pressure for 10-15min.
[0024] In one or more embodiments, the conductive cloth has a thickness of 0.03-0.05 mm.
[0025] In one or more embodiments, the specific process of step S4 is to select acrylic pressure-sensitive adhesive as the adhesive layer and apply it to the other side of the foam, using roller coating technology, and controlling the coating thickness to 0.05-0.06mm; the curing condition is to place it at room temperature for 24-36 hours to allow the adhesive layer to completely cure.
[0026] In one or more embodiments, the specific process of step S5 is: using a PE film as the isolation layer; using a light pressure laminator to laminate at a pressure of 1-1.5 MPa to ensure that the isolation layer is completely attached to the adhesive layer.
[0027] In one or more embodiments, the PE film has a thickness of 0.02-0.03 mm.
[0028] Principle of the present invention:
[0029] The present invention uses nano nickel powder added to carbon nanotube-cerium oxide as a conductive and shielding additive, wherein the nickel powder provides basic conductivity; the carbon nanotube acts as a bridge to enhance the continuity of the conductive path, increase flexibility, and prevent the conductive network from breaking when under pressure; and cerium oxide (CeO2) is a rare earth oxide with excellent electromagnetic absorption properties, especially in the high frequency band (GHz level). It achieves electromagnetic absorption through internal electron transition (Ce 3+ ↔Ce 4+), can absorb electromagnetic waves and convert electromagnetic energy into other forms (such as heat energy) through changes in electronic energy levels, thereby reducing the intensity of electromagnetic waves. In addition, cerium oxide acts as a microparticle scattering center in the material, causing electromagnetic waves to be scattered, absorbed and attenuated multiple times in the shielding material, further enhancing the shielding effectiveness. Therefore, it can work in conjunction with nickel powder and carbon nanotubes to form a multi-level, multi-dimensional shielding structure. At the same time, cerium oxide has good antioxidant properties and can form a protective film on the surface of the material to inhibit the oxidation process of metal materials such as nickel powder, and prevent conductive fillers such as nickel powder from being oxidized in high temperature or humid environments, causing the conductive properties of the material to decrease over time. On the other hand, cerium oxide can also fill tiny gaps in the conductive network and form a fine particle structure, thereby enhancing the close contact between conductive particles, reducing microscopic gaps in the network, and making the conductive path more continuous, thereby improving the overall conductivity of the composite material. Through the synergistic effect of the three, the present invention can achieve a good electromagnetic shielding effect by using an ultra-thin (≤0.8mm) size.
[0030] Since the foam prepared by the present invention is thin in size, when the device is in a continuous thermal cycle and internal mechanical stress, the nickel-carbon shielding foam will have tiny cracks. As these cracks gradually expand and deepen and penetrate the Z direction of the foam, the overall functionality of the shielding foam is affected, the risk of electromagnetic interference is increased, and the performance and reliability of the electronic equipment are reduced. In order to overcome the problems of ultra-thin shielding foams in the prior art, the present invention also adds polyfuran and maleimide. As the device continues to run and generate heat, the self-healing material can re-form a conductive path inside the matrix after repair, and the conductive shielding filler (such as carbon nanotubes, nickel particles, etc.) can restore the conductive performance. The self-healing ability of this network ensures that the material can still maintain good electrical properties after stress damage or cracks. Through the reversible cross-linking system of polyfuran and maleimide, the distribution of the filler can be readjusted during the repair process to avoid permanent damage to the conductive network and ensure the stability of the electronic equipment in long-term operation. In the reversible Diels-Alder reaction system of polyfuran and maleimide-based materials, the introduction of cerium oxide nanoparticles can not only improve the efficiency of the reverse Diels-Alder reaction, but also accelerate the self-healing process through catalysis. The Diels-Alder reaction is a [4+2] cycloaddition reaction, and the cross-linking of polyfuran and maleimide forms a stable covalent bond structure. Under high temperature conditions (such as 120°C), this cross-linking structure can be broken by the reverse Diels-Alder reaction, thereby achieving self-healing function. The key to the reverse Diels-Alder reaction is to break the cyclic structure of the addition product of polyfuran and maleimide, so that the material re-enters the monomer state and then re-cross-links under appropriate conditions. Cerium oxide nanoparticles can affect the reaction path of the reverse Diels-Alder reaction through their surface acid-base sites and oxygen vacancies. The Lewis acid sites on its surface can interact with the electron cloud of the reactants, promote the activation of furan or maleimide molecules, reduce the activation energy required for the reaction, and enable the reverse reaction to proceed at a lower temperature. When the device generates heat during operation, the self-repair function can be activated. The unique oxygen vacancies of CeO2 are conducive to electron transfer. This electron-rich environment can accelerate the recombination of reactants and molecular reorganization. In addition, the redox cycle of cerium oxide (Ce 3+ ↔Ce 4+ ) can provide a dynamic electronic regulation environment for the reverse Diels-Alder reaction, which helps the formation and stabilization of key intermediates in the reaction process, thereby improving the reaction efficiency.
[0031] The technical solution of the present invention can achieve at least one of the following effects:
[0032] (1) Significant electromagnetic shielding effect: The present invention greatly improves the electromagnetic shielding performance of the foam by using a nickel-carbon nanotube-cerium oxide composite material. Nickel particles provide basic conductivity, carbon nanotubes act as a bridge of the conductive network to ensure the continuity of the conductive path, and cerium oxide significantly enhances the electromagnetic shielding effect through its excellent electromagnetic absorption properties, especially the absorption of high-frequency electromagnetic interference (such as GHz level). Therefore, the conductive foam can effectively suppress the high-frequency electromagnetic interference generated in modern electronic devices and ensure the normal operation of the equipment.
[0033] (2) Self-repairing ability to extend the life of foam: The present invention constructs a self-repairing system by adding polyfuran and maleimide. When the foam is subjected to mechanical stress or thermal cycling and cracks are generated during use, the self-repairing material can automatically repair the conductive network through the reverse Diels-Alder reaction and restore the shielding performance and conductivity of the material. This self-repairing function effectively extends the service life of the foam, reduces the frequency of material replacement, and ensures the stability of conductivity and shielding effect under long-term use.
[0034] (3) Ultra-thin design meets the needs of modern electronic devices: With the trend of electronic products becoming thinner and lighter, the thickness of the foam needs to be reduced as much as possible. The present invention achieves an ultra-thin foam design of 0.3 to 0.8 mm, ensuring adaptability in compact spaces, and even at a relatively small thickness, it can still maintain excellent electromagnetic shielding performance, meeting the needs of modern electronic devices for thinness and high-efficiency electromagnetic shielding.
[0035] (4) Excellent conductivity and mechanical strength: The conductive foam of the present invention not only has good electromagnetic shielding ability, but also maintains high strength and flexibility. Through a reasonable combination of materials, carbon nanotubes and cerium oxide form a stable conductive network, while increasing the mechanical strength of the foam, making it less likely to break during dynamic use and installation. The material can still maintain its conductivity and shielding function when subjected to external forces.
[0036] (5) Improved anti-aging and environmental resistance: Due to the addition of nano-cerium oxide, the present invention has excellent anti-oxidation and anti-aging properties, and can maintain long-term stable electromagnetic shielding effects in harsh environments such as high temperature and high humidity. This design ensures the durability of the foam, allowing it to maintain excellent shielding effects under harsh environmental conditions, and reduces material aging and failure problems caused by environmental factors.
[0037] In the present invention, the above-mentioned technical solutions can also be combined with each other to achieve more preferred combination solutions. Other features and advantages of the present invention will be described in the subsequent description, and some advantages can become obvious from the description, or can be understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained through the contents particularly pointed out in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] The drawings are only for the purpose of illustrating particular embodiments and are not to be considered limiting of the present invention. Like reference symbols denote like components throughout the drawings.
[0039] Figure 1 The present invention is a flow chart of the method for preparing nickel-carbon conductive shielding foam. DETAILED DESCRIPTION
[0040] The technical scheme of the present invention is further described below in conjunction with specific embodiments, but the present invention should not be limited to these embodiments. Unless otherwise described, they can be replaced by other alternative features that are equivalent or have similar purposes. Unless otherwise described, each feature is just an example of a series of equivalent or similar features. The terms used in the present invention, unless otherwise specified, generally have the meanings commonly understood by those of ordinary skill in the art. In the following examples, unless otherwise specified, concentration % refers to mass percentage; the substances used can be obtained commercially. The technical scheme of the present invention is further described below in conjunction with specific embodiments, but the present invention should not be limited to these embodiments.
[0041] like Figure 1 The flowchart of the preparation method of the nickel-carbon conductive shielding foam of the present invention is shown.
[0042] The reagents used in the present embodiment and comparative examples are as follows. Those skilled in the art can select appropriate reagents for substitution and still achieve the effects of the present invention. The following reagent selection is not intended to limit the present invention.
[0043] Multi-walled carbon nanotubes were purchased from Chengdu Organic Chemistry Co., Ltd., Chinese Academy of Sciences, Chengdu.
[0044] Cerium oxide nanoparticles, particle size: 4-8 nm, were purchased from Jiangsu Xianfeng Nanotechnology Co., Ltd.
[0045] Nano nickel powder, with an average particle size of 50 nm, YJ-Ni-001 was purchased from Nanjing Yuejing Nanotechnology Co., Ltd.
[0046] Polyfuran with a purity of 99.9% was purchased from Hefei Lifu Biological Co., Ltd.
[0047] Maleimide, purity 99%, was purchased from Qingdao Ruifengyuan Chemical Co., Ltd.
[0048] Dimethyl silicone oil, kinematic viscosity (20°C): 10 mm 2 / s, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.
[0049] Methylvinylsiloxane was purchased from Shanghai Myrel Biochemical Technology Co., Ltd., with a viscosity of 20,000-50,000 cps and a vinyl content of 0.1-0.3%.
[0050] Epoxy resin adhesive was purchased from Ningbo Mingsheng Adhesive Co., Ltd.
[0051] Example 1
[0052] Preparation of foam:
[0053] 10 parts of carbon nanotubes were added to 1500 parts of deionized water, and 0.5 parts of sodium dodecyl sulfate were added, and then the carbon nanotubes were ultrasonically treated for 90 minutes using an ultrasonic treatment device. After the ultrasonic treatment was completed, the dispersed carbon nanotubes were washed twice.
[0054] 10 parts of cerium oxide nanoparticles were added to 1500 parts of deionized water, stirred for 60 minutes using a mechanical stirrer, and then treated with ultrasound for 45 minutes.
[0055] The pretreated carbon nanotubes and cerium oxide nanoparticles are mixed in a mass ratio of 1:0.5, and nano nickel powder is added to the carbon nanotube-cerium oxide mixed solution to form a suspension. The mass ratio of the pretreated carbon nanotubes and nano nickel powder is 1:10.
[0056] Under stirring conditions, the reducing agent ethylene glycol is gradually added for reduction reaction, and the mass ratio of ethylene glycol to nano-nickel is 2:1; the reaction temperature is controlled at 85°C and the time is 2h, so that nickel ions are deposited on the surface of carbon nanotubes and cerium oxide particles, and after filtering, washing with ethanol aqueous solution, and drying, a uniformly coated nickel-carbon nanotube-cerium oxide composite structure is formed.
[0057] Based on the weight components, 25 parts of nickel-carbon nanotube-cerium oxide composite powder and 1 part of ionic liquid dispersant 1-butyl-3-methylimidazolium hexafluorophosphate were dispersed by ultrasonication for 30 minutes.
[0058] 10 parts of organic silicone oil dimethyl silicone oil and 20 parts of silicone rubber methyl vinyl siloxane were uniformly mixed to form the base material.
[0059] 5 parts of polyfuran and 5 parts of maleimide were gradually added into the mixture of organic silicone oil dimethyl silicone oil and silicone rubber methyl vinyl siloxane, and stirred evenly at 60°C.
[0060] Then add 0.5 parts of silane coupling agent KH-560, continue stirring to fully combine the silane coupling agent with the matrix, the stirring speed is 500r / min, the stirring time is 20min, gradually add the dispersed nickel-carbon nanotube-cerium oxide composite powder to the silicone matrix mixture, continue stirring until completely mixed, the stirring speed is 500r / min; the stirring time is 30min, add 0.01 parts of platinum catalyst to the mixed matrix and composite powder, and stir gently, then add 0.2 parts of cross-linking agent methyltriethoxysilane to ensure sufficient mixing, the stirring speed is 300r / min, and the stirring time is 10min.
[0061] Pour the mixture into a mold and cure at 60 °C for 1 h at 45% RH to avoid bubble formation.
[0062] Preparation of nickel-carbon conductive shielding foam:
[0063] The foam thickness is selected to be 0.3-0.8 mm, and 0.5 mm foam is used in this embodiment.
[0064] The conductive layer is made of conductive cloth with a thickness of 0.03 mm. The conductive cloth is aligned with the surface of the foam and the back of the conductive cloth is coated with epoxy resin adhesive. Hot pressing is performed at 120°C and 5 MPa pressure for 10 minutes to ensure a good combination of the conductive cloth and the foam.
[0065] The adhesive layer uses acrylic-based pressure-sensitive adhesive on the other side of the foam, and uses roller coating technology to control the coating thickness at 0.05mm. Curing conditions: leave it at room temperature for 24 hours to allow the adhesive layer to completely cure. The isolation layer uses a PE film with a thickness of 0.02mm. Use a light pressure laminator to laminate at a pressure of 1 MPa to ensure that the isolation layer is completely attached to the adhesive layer. For cutting and forming, use a laser cutting machine to ensure a cutting accuracy of ±0.01mm. For cutting parameters, the laser power is set to 100W and the cutting speed is 200 mm / min. Cut according to customer needs. In this embodiment, the cutting size is 100mm × 100mm× 0.5mm.
[0066] Example 2
[0067] Preparation of foam:
[0068] 10 parts of carbon nanotubes were added to 1500 parts of deionized water, and 0.5 parts of sodium dodecyl sulfate were added, and then the carbon nanotubes were ultrasonically treated for 90 minutes using an ultrasonic treatment device. After the ultrasonic treatment was completed, the dispersed carbon nanotubes were washed twice.
[0069] 10 parts of cerium oxide nanoparticles were added to 1500 parts of deionized water, stirred for 60 minutes using a mechanical stirrer, and then treated with ultrasound for 45 minutes.
[0070] The pretreated carbon nanotubes and cerium oxide nanoparticles are mixed in a mass ratio of 1:0.9, and nano nickel powder is added to the carbon nanotube-cerium oxide mixed solution to form a suspension. The mass ratio of the pretreated carbon nanotubes and nano nickel powder is 1:10.
[0071] Under stirring conditions, the reducing agent ethylene glycol is gradually added for reduction reaction, and the mass ratio of ethylene glycol to nano-nickel is 2:1; the reaction temperature is controlled at 100°C and the reaction time is 3 hours, so that nickel ions are deposited on the surface of carbon nanotubes and cerium oxide particles, and after filtering, washing with ethanol aqueous solution, and drying, a uniformly coated nickel-carbon nanotube-cerium oxide composite structure is formed.
[0072] Based on the weight components, 32 parts of nickel-carbon nanotube-cerium oxide composite powder and 4.5 parts of ionic liquid dispersant 1-butyl-3-methylimidazolium hexafluorophosphate were dispersed by ultrasonication for 60 minutes.
[0073] 20 parts of organic silicone oil dimethyl silicone oil and 35 parts of silicone rubber methyl vinyl siloxane were uniformly mixed to form the base material.
[0074] 10 parts of polyfuran and 10 parts of maleimide were gradually added into the mixture of organic silicone oil dimethyl silicone oil and silicone rubber methyl vinyl siloxane, and stirred evenly at 80°C.
[0075] Then add 3 parts of silane coupling agent KH-550, continue stirring to fully combine the silane coupling agent with the matrix, the stirring speed is 1000r / min, the stirring time is 30min, gradually add the dispersed nickel-carbon nanotube-cerium oxide composite powder to the silicone matrix mixture, continue stirring until completely mixed, the stirring speed is 1000r / min; the stirring time is 60min, add 0.05 parts of platinum catalyst to the mixed matrix and composite powder, and stir gently, then add 1.5 parts of cross-linking agent methyltriethoxysilane, ensure sufficient mixing, the stirring speed is 800r / min, and the stirring time is 20min.
[0076] Pour the mixture into a mold and cure at 80 °C for 3 h at 45% RH to avoid bubble formation.
[0077] Preparation of nickel-carbon conductive shielding foam:
[0078] The foam thickness should be 0.5mm.
[0079] The conductive layer is made of conductive cloth with a thickness of 0.03 mm. The conductive cloth is aligned with the surface of the foam and the back of the conductive cloth is coated with epoxy resin adhesive. Hot pressing is performed at 120°C and 5 MPa pressure for 10 minutes to ensure a good combination of the conductive cloth and the foam.
[0080] The adhesive layer uses acrylic-based pressure-sensitive adhesive on the other side of the foam, and uses roller coating technology to control the coating thickness at 0.05mm. Curing conditions: leave it at room temperature for 24 hours to allow the adhesive layer to completely cure. The isolation layer uses a PE film with a thickness of 0.02mm. Use a light pressure laminator to laminate at a pressure of 1 MPa to ensure that the isolation layer is completely attached to the adhesive layer. For cutting and forming, use a laser cutting machine to ensure a cutting accuracy of ±0.01mm. For cutting parameters, the laser power is set to 100W and the cutting speed is 200 mm / min. Cut according to customer needs. In this embodiment, the cutting size is 100mm × 100mm× 0.5mm.
[0081] Example 3
[0082] Preparation of foam:
[0083] 10 parts of carbon nanotubes were added to 1500 parts of deionized water, and 0.5 parts of sodium dodecyl sulfate were added, and then the carbon nanotubes were ultrasonically treated for 90 minutes using an ultrasonic treatment device. After the ultrasonic treatment was completed, the dispersed carbon nanotubes were washed twice.
[0084] 10 parts of cerium oxide nanoparticles were added to 1500 parts of deionized water, stirred for 60 minutes using a mechanical stirrer, and then treated with ultrasound for 45 minutes.
[0085] The pretreated carbon nanotubes and cerium oxide nanoparticles are mixed in a mass ratio of 1:1, and nano nickel powder is added to the carbon nanotube-cerium oxide mixed solution to form a suspension. The mass ratio of the pretreated carbon nanotubes and nano nickel powder is 1:11.
[0086] Under stirring conditions, the reducing agent ethylene glycol is gradually added for reduction reaction, and the mass ratio of ethylene glycol to nano-nickel is 2:1; the reaction temperature is controlled at 90°C and the reaction time is 2.5 hours, so that nickel ions are deposited on the surface of carbon nanotubes and cerium oxide particles, and after filtering, washing with ethanol aqueous solution, and drying, a uniformly coated nickel-carbon nanotube-cerium oxide composite structure is formed.
[0087] Based on the weight components, 30 parts of nickel-carbon nanotube-cerium oxide composite powder and 3 parts of ionic liquid dispersant 1-butyl-3-methylimidazolium hexafluorophosphate were dispersed by ultrasonication for 45 minutes.
[0088] 15 parts of organic silicone oil methylphenyl silicone oil and 30 parts of silicone rubber methylphenylsiloxane were uniformly mixed to form a base material.
[0089] 8 parts of polyfuran and 8 parts of maleimide were gradually added into the mixture of organic silicone oil methylphenyl silicone oil and silicone rubber methylphenylsiloxane, and stirred evenly at 70°C.
[0090] Then add 2 parts of silane coupling agent KH-570, continue stirring to fully combine the silane coupling agent with the matrix, the stirring speed is 800r / min, the stirring time is 25min, gradually add the dispersed nickel-carbon nanotube-cerium oxide composite powder to the silicone matrix mixture, continue stirring until completely mixed, the stirring speed is 750r / min; the stirring time is 45min, add 0.03 parts of platinum catalyst to the mixed matrix and composite powder, and stir gently, then add 1 part of cross-linking agent methyltriethoxysilane to ensure sufficient mixing, the stirring speed is 500r / min, and the stirring time is 15min.
[0091] Pour the mixture into a mold and cure at 70 °C for 1 h at 45% RH to avoid bubble formation.
[0092] Preparation of nickel-carbon conductive shielding foam:
[0093] In this embodiment, 0.5 mm foam is used.
[0094] The conductive layer is made of conductive cloth with a thickness of 0.03 mm. The conductive cloth is aligned with the surface of the foam and the back of the conductive cloth is coated with epoxy resin adhesive. Hot pressing is performed at 120°C and 5 MPa pressure for 10 minutes to ensure a good combination of the conductive cloth and the foam.
[0095] The adhesive layer uses acrylic-based pressure-sensitive adhesive on the other side of the foam, and uses roller coating technology to control the coating thickness at 0.05mm. Curing conditions: leave it at room temperature for 24 hours to allow the adhesive layer to completely cure. The isolation layer uses a PE film with a thickness of 0.02mm. Use a light pressure laminator to laminate at a pressure of 1 MPa to ensure that the isolation layer is completely attached to the adhesive layer. For cutting and forming, use a laser cutting machine to ensure a cutting accuracy of ±0.01mm. For cutting parameters, the laser power is set to 100W and the cutting speed is 200 mm / min. Cut according to customer needs. In this embodiment, the cutting size is 100mm × 100mm× 0.5mm.
[0096] Example 4
[0097] Preparation of foam:
[0098] 10 parts of carbon nanotubes were added to 1500 parts of deionized water, and 0.5 parts of sodium dodecyl sulfate were added, and then the carbon nanotubes were ultrasonically treated for 90 minutes using an ultrasonic treatment device. After the ultrasonic treatment was completed, the dispersed carbon nanotubes were washed twice.
[0099] 10 parts of cerium oxide nanoparticles were added to 1500 parts of deionized water, stirred for 60 minutes using a mechanical stirrer, and then treated with ultrasound for 45 minutes.
[0100] The pretreated carbon nanotubes and cerium oxide nanoparticles are mixed in a mass ratio of 1:1, and nano nickel powder is added to the carbon nanotube-cerium oxide mixed solution to form a suspension. The mass ratio of the pretreated carbon nanotubes and nano nickel powder is 1:10.
[0101] Under stirring conditions, the reducing agent ethylene glycol is gradually added for reduction reaction, and the mass ratio of ethylene glycol to nano-nickel is 2:1; the reaction temperature is controlled at 90°C and the reaction time is 2.5 hours, so that nickel ions are deposited on the surface of carbon nanotubes and cerium oxide particles, and after filtering, washing with ethanol aqueous solution, and drying, a uniformly coated nickel-carbon nanotube-cerium oxide composite structure is formed.
[0102] Based on the weight components, 35 parts of nickel-carbon nanotube-cerium oxide composite powder and 4 parts of ionic liquid dispersant 1-butyl-3-methylimidazolium hexafluorophosphate were dispersed by ultrasonication for 50 minutes.
[0103] 22 parts of organic silicone oil dimethyl silicone oil and 35 parts of silicone rubber methyl vinyl siloxane were uniformly mixed to form the base material.
[0104] 7 parts of polyfuran and 9 parts of maleimide were gradually added into the mixture of organic silicone oil dimethyl silicone oil and silicone rubber methyl vinyl siloxane, and stirred evenly at 75°C.
[0105] Then add 1.6 parts of silane coupling agent KH-570, continue stirring to fully combine the silane coupling agent with the matrix, the stirring speed is 600r / min, the stirring time is 30min, gradually add the dispersed nickel-carbon nanotube-cerium oxide composite powder to the silicone matrix mixture, continue stirring until completely mixed, the stirring speed is 750r / min; the stirring time is 45min, add 0.03 parts of platinum catalyst to the mixed matrix and composite powder, and stir gently, then add 1.2 parts of cross-linking agent methyltriethoxysilane to ensure sufficient mixing, the stirring speed is 600r / min, and the stirring time is 18min.
[0106] Pour the mixture into a mold and cure at 70 °C for 2.5 h and 45% RH to avoid bubble formation.
[0107] Preparation of nickel-carbon conductive shielding foam:
[0108] The foam thickness should be 0.5mm.
[0109] The conductive layer is made of conductive cloth with a thickness of 0.03 mm. The conductive cloth is aligned with the surface of the foam and the back of the conductive cloth is coated with epoxy resin adhesive. Hot pressing is performed at 120°C and 5 MPa pressure for 10 minutes to ensure a good combination of the conductive cloth and the foam.
[0110] The adhesive layer uses acrylic-based pressure-sensitive adhesive on the other side of the foam, and uses roller coating technology to control the coating thickness at 0.05mm. Curing conditions: leave it at room temperature for 24 hours to allow the adhesive layer to completely cure. The isolation layer uses a PE film with a thickness of 0.02mm. Use a light pressure laminator to laminate at a pressure of 1 MPa to ensure that the isolation layer is completely attached to the adhesive layer. For cutting and forming, use a laser cutting machine to ensure a cutting accuracy of ±0.01mm. For cutting parameters, the laser power is set to 100W and the cutting speed is 200 mm / min. Cut according to customer needs. In this embodiment, the cutting size is 100mm × 100mm× 0.5mm.
[0111] Comparative Example 1
[0112] Preparation of foam:
[0113] 10 parts of carbon nanotubes were added to 1500 parts of deionized water, and 0.5 parts of sodium dodecyl sulfate were added, and then the carbon nanotubes were ultrasonically treated for 90 minutes using an ultrasonic treatment device. After the ultrasonic treatment was completed, the dispersed carbon nanotubes were washed twice.
[0114] Nano nickel powder is added into the carbon nano tube mixed solution to form a suspension, wherein the mass ratio of the pretreated carbon nano tube to the nano nickel powder is 1:10.
[0115] Under stirring conditions, the reducing agent ethylene glycol is gradually added for reduction reaction, and the mass ratio of ethylene glycol to nano-nickel is 2:1; the reaction temperature is controlled at 90°C and the reaction time is 2.5 hours, so that nickel ions are deposited on the surface of carbon nanotubes and cerium oxide particles, and after filtering, washing with ethanol aqueous solution, and drying, a uniformly coated nickel-carbon nanotube composite structure is formed.
[0116] Based on the weight components, 35 parts of nickel-carbon nanotube composite powder and 4 parts of ionic liquid dispersant 1-butyl-3-methylimidazolium hexafluorophosphate were dispersed using ultrasonic waves for 50 minutes.
[0117] 22 parts of organic silicone oil dimethyl silicone oil and 35 parts of silicone rubber methyl vinyl siloxane were uniformly mixed to form the base material.
[0118] 7 parts of polyfuran and 9 parts of maleimide were gradually added into the mixture of organic silicone oil dimethyl silicone oil and silicone rubber methyl vinyl siloxane, and stirred evenly at 75°C.
[0119] Then add 1.6 parts of silane coupling agent KH-570, continue stirring to fully combine the silane coupling agent with the matrix, the stirring speed is 600r / min, the stirring time is 30min, gradually add the dispersed nickel-carbon nanotube composite powder to the silicone matrix mixture, continue stirring until completely mixed, the stirring speed is 750r / min; the stirring time is 45min, add 0.03 parts of platinum catalyst to the mixed matrix and composite powder, and stir gently, then add 1.2 parts of cross-linking agent methyltriethoxysilane, ensure sufficient mixing, the stirring speed is 600r / min, and the stirring time is 18min.
[0120] Pour the mixture into a mold and cure at 70 °C for 2.5 h and 45% RH to avoid bubble formation.
[0121] Preparation of nickel-carbon conductive shielding foam:
[0122] The foam thickness should be 0.5mm.
[0123] The conductive layer is made of conductive cloth with a thickness of 0.03 mm. The conductive cloth is aligned with the surface of the foam and the back of the conductive cloth is coated with epoxy resin adhesive. Hot pressing is performed at 120°C and 5 MPa pressure for 10 minutes to ensure a good combination of the conductive cloth and the foam.
[0124] The adhesive layer uses acrylic-based pressure-sensitive adhesive on the other side of the foam, and uses roller coating technology to control the coating thickness at 0.05mm. Curing conditions: leave it at room temperature for 24 hours to allow the adhesive layer to completely cure. The isolation layer uses a PE film with a thickness of 0.02mm. Use a light pressure laminator to laminate at a pressure of 1 MPa to ensure that the isolation layer is completely attached to the adhesive layer. For cutting and forming, use a laser cutting machine to ensure a cutting accuracy of ±0.01mm. For cutting parameters, the laser power is set to 100W and the cutting speed is 200 mm / min. Cut according to customer needs. In this embodiment, the cutting size is 100mm × 100mm× 0.5mm.
[0125] Compared with Example 4, Comparative Example 1 omitted the addition of cerium oxide, and the remaining operation procedures and process parameters were the same.
[0126] Comparative Example 2
[0127] Preparation of foam:
[0128] 10 parts of carbon nanotubes were added to 1500 parts of deionized water, and 0.5 parts of sodium dodecyl sulfate were added, and then the carbon nanotubes were ultrasonically treated for 90 minutes using an ultrasonic treatment device. After the ultrasonic treatment was completed, the dispersed carbon nanotubes were washed twice.
[0129] 10 parts of cerium oxide nanoparticles were added to 1500 parts of deionized water, stirred for 60 minutes using a mechanical stirrer, and then treated with ultrasound for 45 minutes.
[0130] The pretreated carbon nanotubes and cerium oxide nanoparticles are mixed in a mass ratio of 1:1, and nano nickel powder is added to the carbon nanotube-cerium oxide mixed solution to form a suspension. The mass ratio of the pretreated carbon nanotubes and nano nickel powder is 1:10.
[0131] Under stirring conditions, the reducing agent ethylene glycol is gradually added for reduction reaction, and the mass ratio of ethylene glycol to nano-nickel is 2:1; the reaction temperature is controlled at 90°C and the reaction time is 2.5 hours, so that nickel ions are deposited on the surface of carbon nanotubes and cerium oxide particles, and after filtering, washing with ethanol aqueous solution, and drying, a uniformly coated nickel-carbon nanotube-cerium oxide composite structure is formed.
[0132] Based on the weight components, 35 parts of nickel-carbon nanotube-cerium oxide composite powder and 4 parts of ionic liquid dispersant 1-butyl-3-methylimidazolium hexafluorophosphate were dispersed by ultrasonication for 50 minutes.
[0133] 22 parts of organic silicone oil dimethyl silicone oil and 35 parts of silicone rubber methyl vinyl siloxane were uniformly mixed to form the base material.
[0134] Then add 1.6 parts of silane coupling agent KH-570, continue stirring to fully combine the silane coupling agent with the matrix, the stirring speed is 600r / min, the stirring time is 30min, gradually add the dispersed nickel-carbon nanotube-cerium oxide composite powder to the silicone matrix mixture, continue stirring until completely mixed, the stirring speed is 750r / min; the stirring time is 45min, add 0.03 parts of platinum catalyst to the mixed matrix and composite powder, and stir gently, then add 1.2 parts of cross-linking agent methyltriethoxysilane to ensure sufficient mixing, the stirring speed is 600r / min, and the stirring time is 18min.
[0135] Pour the mixture into a mold and cure at 70 °C for 2.5 h and 45% RH to avoid bubble formation.
[0136] Preparation of nickel-carbon conductive shielding foam:
[0137] The foam thickness should be 0.5mm.
[0138] The conductive layer is made of conductive cloth with a thickness of 0.03 mm. The conductive cloth is aligned with the surface of the foam and the back of the conductive cloth is coated with epoxy resin adhesive. Hot pressing is performed at 120°C and 5 MPa pressure for 10 minutes to ensure a good combination of the conductive cloth and the foam.
[0139] The adhesive layer uses acrylic-based pressure-sensitive adhesive on the other side of the foam, and uses roller coating technology to control the coating thickness at 0.05mm. Curing conditions: leave it at room temperature for 24 hours to allow the adhesive layer to completely cure. The isolation layer uses a PE film with a thickness of 0.02mm. Use a light pressure laminator to laminate at a pressure of 1 MPa to ensure that the isolation layer is completely attached to the adhesive layer. For cutting and forming, use a laser cutting machine to ensure a cutting accuracy of ±0.01mm. For cutting parameters, the laser power is set to 100W and the cutting speed is 200 mm / min. Cut according to customer needs. In this embodiment, the cutting size is 100mm × 100mm× 0.5mm.
[0140] Compared with Example 4, Comparative Example 2 omitted the addition of polyfuran and maleimide, and the remaining operation procedures and process parameters were the same.
[0141] The nickel-carbon conductive shielding foam obtained in Examples 1-4 and Comparative Examples 1-2 was subjected to performance testing, and the specific testing methods and evaluation criteria were as follows:
[0142] Conductivity test (four-point probe method),
[0143] Prepare a foam sample of 10 mm × 10 mm × 0.5 mm in size and ensure that the surface is flat and free of contamination. Place the sample on the test platform and ensure that the probe evenly contacts the sample surface.
[0144] For electromagnetic shielding effectiveness (SE) test, the equipment uses an EMI shielding effectiveness tester (refer to ASTM D4935 or IEC61000-4-3 standard).
[0145] The foam was cut into round samples with a diameter of 80 mm and a thickness of 0.5 mm. The test frequency bands were set to 30 MHz- 0.5 GHz and 3 GHz - 10 GHz, and the measurement results were taken as the average value in this range.
[0146] The electromagnetic signal intensity (E0) was measured in the absence of sample.
[0147] Place the foam sample and measure the electromagnetic signal intensity (E1) again.
[0148] Calculate shielding effectiveness according to the formula: SE (dB) = 10 log (E0 / E1).
[0149] Self-repair function detection: recovery test of electromagnetic shielding performance.
[0150] (1) Electromagnetic shielding effectiveness test before damage.
[0151] A complete foam sample (80 mm in diameter and 0.5 mm in thickness) was prepared.
[0152] Use an EMI shielding effectiveness tester to test the shielding effectiveness (SE value) of the foam, with a frequency range of 30 MHz - 0.5GHz. Record the average SE value of the sample as a reference value for the original shielding effectiveness.
[0153] (2) Electromagnetic shielding effectiveness test after damage.
[0154] Apply certain mechanical damage to the foam sample, use a cutting tool to create a 0.1mm crack on the foam surface, and use the EMI test equipment to test the electromagnetic shielding effectiveness (SE average value) of the damaged sample again.
[0155] (3) Electromagnetic shielding effectiveness recovery test after self-repair.
[0156] Place the damaged foam sample in a 120°C environment (simulating the temperature reached when an electronic device is running and generating heat) for 1 hour to start the Diels-Alder reaction of the self-healing function in the material. After the repair is completed, use EMI testing equipment to test the electromagnetic shielding effectiveness of the self-healed sample. Record the SE value after repair and compare it with the SE value before and after damage to evaluate the repair effect.
[0157] Evaluation criteria: SE value recovery rate: By calculating the recovery rate of electromagnetic shielding effectiveness after repair, the impact of the self-repair function on the shielding performance is quantified.
[0158] Calculation formula: Shielding effectiveness recovery rate (%) = (SE value after repair / SE value before damage) × 100%.
[0159] The test results are shown in Table 1.
[0160]
[0161] As can be seen from Table 1, in Examples 1-4, the conductivity is gradually improved with the optimization of the material formula. The change in conductivity reflects the synergistic effect between carbon nanotubes, nickel powder and cerium oxide.
[0162] Comparative Example 1 (without cerium oxide): The conductivity is only 0.63 × 10³ S / m, which is much lower than that of other examples. The lack of cerium oxide makes the conductive network incomplete and unable to form a stable conductive path, resulting in a significant decrease in conductivity.
[0163] Comparative Example 2 (no self-healing material): The conductivity is 1.05 × 10³ S / m. Although it lacks self-healing function, it is still higher than that of Comparative Example 1 because cerium oxide still exists and helps form a more stable conductive network.
[0164] Electromagnetic shielding effectiveness (SE value) analysis:
[0165] Low frequency band (30 MHz - 0.5 GHz): The SE value of Comparative Example 1 is only 48 dB, which is much lower than that of the examples, indicating that the absence of cerium oxide greatly affects the shielding effectiveness.
[0166] High frequency band (3 GHz - 10 GHz):
[0167] The SE value of comparative example 1 dropped significantly to only 26 dB, which once again verified the key role of cerium oxide in high-frequency shielding.
[0168] Shielding effectiveness and recovery rate after repair:
[0169] The SE value of Example 4 after repair is 53 dB, and the recovery rate is 84.1%. This is because the self-healing system of polyfuran and maleimide can effectively restore the integrity of the conductive network, and cerium oxide also helps to rebuild the conductive network during the repair process.
[0170] The SE value of comparative example 1 after repair is only 27 dB, and the recovery rate is only 56.2%, indicating that the lack of the introduction of cerium oxide nanoparticles makes the self-repair reaction slow and performs poorly in practical repair.
[0171] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.
Claims
1. A method for preparing a nickel-carbon conductive shielding foam, characterized in that: The steps include: S1: pretreated carbon nanotubes and cerium oxide nanoparticles are mixed in proportion, and nano nickel powder is added to form a suspension; a reducing agent is added under stirring conditions to perform a reduction reaction, so as to deposit nickel ions on the surfaces of the carbon nanotubes and cerium oxide particles to obtain a nickel-carbon nanotube-cerium oxide composite powder; S2: After mixing the nickel-carbon nanotube-cerium oxide composite powder with the ionic liquid dispersant, use ultrasonic dispersion; then mix the silicone oil and silicone rubber as a matrix, then gradually add polyfuran and maleimide to the matrix, and add a silane coupling agent to fully combine; add the dispersed composite powder to the silicone matrix, continue stirring until the mixture is uniform, then add a platinum catalyst and a cross-linking agent, and pour the mixture into a mold to solidify to form a foam; S3: Paste the conductive layer, coat the foam with epoxy resin adhesive and then hot press the conductive layer onto one side of the foam; S4: Setting an adhesive layer, using an acrylic-based pressure-sensitive adhesive, coating it on the other side of the foam and curing it; S5: Setting an isolation layer, and using a light pressure laminator to laminate the isolation layer to the adhesive layer; The specific process of step S1 is: adding carbon nanotubes into deionized water, adding sodium dodecyl sulfate and then using ultrasonic treatment equipment to ultrasonically treat the carbon nanotubes for 1-2 hours. After the ultrasonic treatment is completed, the dispersed carbon nanotubes are washed 2-3 times. The cerium oxide nanoparticles were added to deionized water, stirred with a mechanical stirrer for 30-60 minutes, and then treated with ultrasound for 30-60 minutes; The pretreated carbon nanotubes and cerium oxide nanoparticles are mixed in a mass ratio of 1:0.5-1.5, and nano-nickel powder is added to the carbon nanotube-cerium oxide mixed solution to form a suspension, wherein the mass ratio of the pretreated carbon nanotubes to the nano-nickel powder is 1:10-12; Under stirring conditions, a reducing agent is gradually added to carry out a reduction reaction, and the reaction temperature is controlled at 80-100°C for 2-3 hours, so that nickel ions are deposited on the surface of carbon nanotubes and cerium oxide particles to form a uniformly coated nickel-carbon nanotube-cerium oxide composite structure.
2. The method for preparing the nickel-carbon conductive shielding foam according to claim 1, characterized in that: The specific process of step S2 is to disperse 25-40 parts of nickel-carbon nanotube-cerium oxide composite powder and 1-5 parts of ionic liquid dispersant by weight for 30-60 minutes using ultrasonic wave; 10-25 parts of silicone oil and 20-40 parts of silicone rubber are uniformly mixed to form a base material; Gradually add 5-10 parts of polyfuran and 5-10 parts of maleimide into the mixture of silicone oil and silicone rubber, and stir evenly at 60-80°C; Then add 0.5-3 parts of silane coupling agent, continue stirring to make the silane coupling agent and the matrix fully combined, gradually add the dispersed nickel-carbon nanotube-cerium oxide composite powder into the silicone matrix mixture, continue stirring until it is completely mixed, the stirring speed is 500-1000r / min; the stirring time is 30-60min, add 0.01-0.05 parts of platinum catalyst to the evenly mixed matrix and composite powder, and gently stir evenly, then add 0.2-1.5 parts of cross-linking agent and mix thoroughly; pour the mixture into a mold for curing and molding.
3. The method for preparing the nickel-carbon conductive shielding foam according to claim 1, characterized in that: The specific process of step S3 is to select conductive cloth as the conductive layer, align the conductive cloth with the foam surface, coat the back of the conductive cloth with epoxy resin adhesive, and perform hot pressing at 120℃-140℃ and 5-6MPa pressure for 10-15min.
4. The method for preparing the nickel-carbon conductive shielding foam according to claim 3, characterized in that: The thickness of the conductive cloth is 0.03-0.05 mm.
5. The method for preparing the nickel-carbon conductive shielding foam according to claim 1, characterized in that: The specific process of step S4 is to select acrylic pressure-sensitive adhesive as the adhesive layer and apply it to the other side of the foam, using roller coating technology, and controlling the coating thickness to be 0.05-0.06mm; the curing condition is to place it at room temperature for 24-36 hours to completely cure the adhesive layer.
6. The method for preparing the nickel-carbon conductive shielding foam according to claim 1, characterized in that: The specific process of step S5 is: using a PE film as an isolation layer; using a light pressure laminator to laminate at a pressure of 1-1.5 MPa to ensure that the isolation layer is completely attached to the adhesive layer.
7. The method for preparing the nickel-carbon conductive shielding foam according to claim 6, characterized in that: The thickness of the PE film is 0.02-0.03 mm.
Citation Information
Patent Citations
Composition and method for forming electroactive coating comprising conjugated heteroaromatic polymer, capacitor and antistatic object comprising the electroactive coating, and solid electrolytic capacitor and method for fabricating the same
CN105295008A
Electrochemical device and electronic device
CN114175299A
Cited By
Flame-retardant environment-friendly rubber material and preparation method thereof
CN120795624A
Flame-retardant environment-friendly rubber material and preparation method thereof
CN120795624B